Intimidations and Assistances of Deep and Dark Web in Modern Era - Singh, Hardeep (International Journal of Computer Sciences and Engineering, 2025)
Deep web harvesting is the necessity of the time. Deep web, also known as invisible web or hidden web is that portion of the World Wide Web from where the contents present cannot be fetched or indexed by traditional search engines such as Google, Yahoo, Excite, Bing etc. due to some technical limitations in them (Devine and Egger-Sider, 2001). A subset of deep web is the dark web. A Dark web is an overlay network that can only be accessed with specific software, configurations, or authorization, often using non-standard communications protocols and ports. Dark web is the stuff of crime novels. It is a hotbed of criminal activity where anything can be bought and sold. The Dark web is a dangerous place where illicit or underground activities are conducted. Dark web is a pool of black market which includes web sites that allow selling and purchasing of items such as hacking software/malware, counterfeit money, drugs, guns etc. The deep web and the dark web are estimated to be literally thousands of time larger than the visible web. This paper initially defines different layers of the web. The paper also explores the threats that the dark web possess to the modern world. In addition to this, the paper also elucidates the importance of deep web harvesting in our daily lives and explores the tools that could be used to find useful resources buried inside the deep web.